2021
DOI: 10.1016/j.eats.2020.10.064
|View full text |Cite
|
Sign up to set email alerts
|

How to Evaluate and Treat Skeletally Mature Patients With Patellar Dislocation

Abstract: Although patellar dislocation is a knee disorder prevalent in adolescence and young adults, the evaluation and treatment of patients are complex and even enigmatic. Much of the literature fails to provide a detailed description of patient management. The purpose of this study is to introduce a method for the evaluation and treatment of patellar dislocation. This Technical Note will help guide clinicians in the clinical evaluation of patients and formulation of treatment plans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Although the standard of care for first-time patellar dislocation is to obtain an MRI scan, recurrent dislocators may have not received an MRI scan initially and the question now becomes, Was the MRI scan conducted for articular cartilage damage concerns or preoperative imaging to guide surgery? 29 Further study is warranted to determine the biomechanics of cartilage injury between the intact and deficient medial patellofemoral ligament state, as well as between male and female patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although the standard of care for first-time patellar dislocation is to obtain an MRI scan, recurrent dislocators may have not received an MRI scan initially and the question now becomes, Was the MRI scan conducted for articular cartilage damage concerns or preoperative imaging to guide surgery? 29 Further study is warranted to determine the biomechanics of cartilage injury between the intact and deficient medial patellofemoral ligament state, as well as between male and female patients.…”
Section: Discussionmentioning
confidence: 99%
“…A TT-TG distance of at least 20 mm has been used widely as an indicator for TTO surgery. 5 , 7 , 21 , 31 , 34 However, the measurement of TT-TG distance has poor reproducibility in patients with trochlear dysplasia, especially in high-grade trochlear dysplasia. 6 , 12 , 14 Dejour et al 5 reported that 96% of patients with patellar dislocation had trochlear dysplasia.…”
Section: Discussionmentioning
confidence: 99%